2014
DOI: 10.2147/ijn.s66000
|View full text |Cite
|
Sign up to set email alerts
|

Nanouric acid or nanocalcium phosphate as central nidus to induce calcium oxalate stone formation: a high-resolution transmission electron microscopy study on urinary nanocrystallites

Abstract: Purpose This study aimed to accurately analyze the relationship between calcium oxalate (CaOx) stone formation and the components of urinary nanocrystallites. Method High-resolution transmission electron microscopy (HRTEM), selected area electron diffraction, fast Fourier transformation of HRTEM, and energy dispersive X-ray spectroscopy were performed to analyze the components of these nanocrystallites. Results The main components of CaOx sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…6). The results of the distribution form of CaOx crystals by XRD in this study looked similar to the pattern of CaOx crystals analyzed by Gao et al . (2014), Shang et al (2013), and Murray et al (2016).…”
Section: Identification Of Caox Crystalssupporting
confidence: 91%
“…6). The results of the distribution form of CaOx crystals by XRD in this study looked similar to the pattern of CaOx crystals analyzed by Gao et al . (2014), Shang et al (2013), and Murray et al (2016).…”
Section: Identification Of Caox Crystalssupporting
confidence: 91%
“…Also, rather than fructose itself, high fructose corn syrup, which is the industry standard sweetener for soda and many foods, has to be considered as a potential risk factor ( 25 , 26 ). Using high-resolution transmission electron microscopy, Gao et al have shown that both nano-uric acid and nano-calcium phosphate may serve as nidus for USD formation ( 27 ).…”
Section: Potential Explanations For the Sex Disparity In Urinary Ston...mentioning
confidence: 99%
“…Higher serum calcium concentration acts as a promoter in lithogenesis, which directly regulated by the calcium-sensing receptor (CaSR) through different pathways ( 35 ). Similarly, urate and phosphate ions have also been reported to promote heterogeneous nucleation and enhance the attachment of crystals to epitheliums ( 36 , 37 ). Another important promoter of stone formation is urine pH ( 38 ).…”
Section: Physicochemical Mechanism Of Kidney Stone Formationmentioning
confidence: 99%